2008
DOI: 10.1002/cmr.b.20102
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the induced fields in MRI occupational workers by lowering the imager

Abstract: In magnetic resonance imaging (MRI), healthcare workers can be exposed to strong static and time-varying magnetic fields outside the imager. Body motion through the large, spatially nonuniform static magnetic field generated by the main magnet and exposure to low-frequency magnetic fields from pulsed gradient coils can lead to the stimulation of electric fields in the body. Tissue of the central and peripheral nervous system (CPNS) in the head and torso is particularly susceptible. To protect occupational work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Moreover, the number of situations where the absolute maximum EI falls within the CNS reduces passing from model SM to TM. These data confirm the results of a previous study (30), where it was shown that the increase of the vertical distance between the head of the operator and the axis of a tubular scanner (eg, by using elevation platforms or scanners embedded into the ground floor) can lead to significant reduction of the exposure levels.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the number of situations where the absolute maximum EI falls within the CNS reduces passing from model SM to TM. These data confirm the results of a previous study (30), where it was shown that the increase of the vertical distance between the head of the operator and the axis of a tubular scanner (eg, by using elevation platforms or scanners embedded into the ground floor) can lead to significant reduction of the exposure levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, operating the z-gradient coil at above $26 mT/m could potentially result in the excitation of peripheral nerves for the herein assumed model conditions. It is noted that these preliminary findings are quite similar to those of recent studies (14,24), which in effect to a certain extent validate the earlier models that relied on theoretical rather than realistic gradient sets.…”
Section: Discussionsupporting
confidence: 88%
“…Gradient coil equipment is expensive/intricate, noisy, power and space demanding, and can induce complex spatiotemporal eddy currents in nearby conducting structures, including the patient [ 2 4 ]. Gradient switching rates are limited by regulatory agencies to avoid peripheral nerve stimulation [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%